Regional Rural Banks and Financial Inclusion: Performance of Tertiary Sector in India (International Journal of Food and Nutritional Sciences, 2021)
This study looks at how Regional Rural Banks (RRBs) support financial inclusion and how their success affects India's tertiary sector. We use data from the last ten years and a variety of statistical techniques to examine the effectiveness and reach of RRBs in rural regions, their role in promoting financial inclusion, and the impact they have had on the expansion of the tertiary sector. Our research shows that RRBs have significantly increased financial inclusion, and that this success has strong associations with the growth of the tertiary sector in rural India. Sustainable growth strategies, financial literacy, and technology adoption continue to be obstacles. For researchers, financial institutions, and policymakers interested in financial inclusion and rural development initiatives in developing nations, this study offers insightful information.